Monocytes and Macrophages as Protagonists in Vascular Complications of Diabetes - Kanter, Jenny E.; Hsu, Cheng-Chieh; Bornfeldt, Karin E. (Frontiers in Cardiovascular Medicine, 2020)
With the increasing prevalence of diabetes worldwide, vascular complications of diabetes are also on the rise. Diabetes results in an increased risk of macrovascular complications, with atherosclerotic cardiovascular disease (CVD) being the leading cause of death in adults with diabetes. The exact mechanisms for how diabetes promotes CVD risk are still unclear, although it is evident that monocytes and macrophages are key players in all stages of atherosclerosis both in the absence and presence of diabetes, and that phenotypes of these cells are altered by the diabetic environment. Evidence suggests that at least five pro-atherogenic mechanisms involving monocytes and macrophages contribute to the accelerated atherosclerotic lesion progression and hampered lesion regression associated with diabetes. These changes include 1) increased monocyte recruitment to lesions; 2) increased inflammatory activation; 3) altered lipid accumulation and metabolism; 4) increased macrophage cell death; and 5) reduced efferocytosis. Monocyte and macrophage phenotypes and mechanisms have been revealed mostly by different animal models of diabetes. The roles of specific changes in monocytes and macrophages in humans with diabetes remain largely unknown. There is an ongoing debate on whether the changes in monocytes and macrophages are caused by altered glucose levels, insulin deficiency or insulin resistance, lipid abnormalities, or combinations of these factors. Current research in humans and mouse models suggests that reduced clearance of triglyceride-rich lipoproteins and their remnants is one important mechanism whereby diabetes adversely affects macrophages and promotes atherosclerosis and CVD risk. Although monocytes and macrophages readily respond to the diabetic environment and can be seen as protagonists in diabetes-accelerated atherosclerosis, they are likely not instigators of the increased CVD risk.